IMPLEMENTASI STRATEGI DINAS LINGKUNGAN HIDUP KOTA PEMATANGSIANTAR DALAM MENGATASI DAMPAK PENCEMARAN LINGKUNGAN DI TPA TANJUNG PINGGIR - Poppy Nadia Sidauruk; Jonson Rajagukguk; Maringan Panjaitan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study is motivated by the condition of the Tanjung Pinggir Final Disposal Site (TPA) in Kota Pematangsiantar, which has experienced overcapacity and still applies an open dumping system, resulting in air, water, and soil pollution as well as public health disturbances. The research aims to analyze the implementation of strategies carried out by the Dinas Lingkungan Hidup Kota Pematangsiantar in addressing environmental pollution impacts. The study is grounded in the implementation theory of Van Meter and Van Horn, environmental management strategy theory, environmental pollution theory, and regional autonomy theory. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. Informants included the Head of the Environmental Agency, landfill field officers, and local community representatives. The findings indicate that technical, operational, educational, and collaborative strategies have been implemented, including waste compaction, leachate control, environmental monitoring, and 3R socialization. However, the implementation remains suboptimal due to budget limitations, inadequate facilities, landfill capacity constraints, and low community participation. It is concluded that although the strategies have been implemented, their effectiveness requires further strengthening through improved resources and more sustainable waste management systems.